Simulasi Manajemen Bencana Dapat Meningkatkan Pengetahuan dan Skill Mahasiswa Keperawatan: Literature Review - Putu Juni Andika; Sri Sundari (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Indonesia has a very high level of disaster vulnerability. Earthquake disasters can occur at any time without being predicted. It is important to implement disaster management simulations in nursing learning to improve the knowledge and skills of nursing students. This paper purpose to find out whether disaster simulation can improve the knowledge and skills of nursing students. This literature uses inclusion and exclusion criteria, articles obtained and reviewed from databases namely Google Scholar (2008 - 2018) and PubMed (2008 - 2018). The search strategy and terminology used in English is as follows: simulation OR disaster or earthquake OR knowledge OR nursing student.  Ten articles were obtained from search results. Eight articles mention earthquake disaster simulations significantly increasing student knowledge and skills. While the two articles stated that disaster management simulation does not increase knowledge but increases attitudes or familiarity in the team and satisfaction. Disaster simulation is one of the methods and strategies in a learning system that has a positive impact, especially in the field of nursing education, especially in response to earthquake management?